Goiânia uma cidade de migrantes - Alves, Maria de Lourdes (2002)
This dissertation analyses the migrations to Goiânia, Objecting your factors, in several historical moments. Firstly, it is necessary to built a theorical model that be able to explain the question of people’s migration in some important moments of the Brazilian history. Secondly, it is necessary to study the occupation s process of Goiás, analysing the several points of expansion of the frontiers in the state: they have in common the fact of them be expansion’s mechanisms of processes situated in dynamic centres of the country. Each on of these processes is particularly analysed, in your specification and adequation to the theorical model proposed. Finally, is mad a quick retrospective about the historical trajectory of Goiânia, and the immigrants arrival, since the Goiânia s building until the 90 s of the 20th century analysing important question like the beginning of the migrations to Goiânia city, and the great growth of the city due to these migrations.